Fatigue Strength Analysis of Bogie Frame In Consideration of Parameter Uncertainty (Fracture and Structural Integrity, 2019)
In this paper, a fatigue strength analysis approach based on Goodman-Smith fatigue limit diagram （GSFLD） and reliability theory is proposed to solve the problem that the traditional fatigue strength analysis of bogie frame is too conservative, considering the parameter uncertainty in engineering practice. Firstly, according to UIC615-4, EN13749 standard and GSFLD, the fatigue strength of the frame is calculated. The experimental results are compared with the simulation data to determine the location of the higher fatigue strength as the control point for the strength evaluation. Secondly, the parametric model of the frame is established by APDL language, and the D-optimal experiment design of uncertainty parameters is carried out. The polynomial response surface function with the mean stress and stress amplitude of the control point as the objective is established. The control points under the influence of uncertainty parameters are obtained by importance sampling method. Finally, the functional expression of GSFLD without considering the safety factor is derived, and the fatigue strength reliability of control point is calculated. The results of this study not only reveal the influence of parameter uncertainty on fatigue strength, but also demonstrate a need of developing new evaluation methods to accommodate fatigue analysis.
Keywords: Bogie frame; Fatigue strength; Goodman-Smith fatigue limit diagram; Response surface; Fatigue reliability